Sosialisasi Manajemen Investasi Melalui Produk Deposito Berjangka Pada Layanan Perbankan Digital - Firmansyah, Alfin Cahya; Rahmawati, Herlini Sanika; Darmawan, Indra Manggala Dwi; Kartini, Ida Ayu Nuh (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This community service activity aims to improve participants’ understanding of investment management through SeaBank's time deposit products. The activity employed a qualitative approach involving 30 sales employees of JAECOO in the automotive sector. The program was conducted through face-to-face socialization using lecture-based methods supported by presentation media, as well as hands-on practice in opening time deposits via the SeaBank mobile application. The materials delivered included fundamental concepts of investment management, characteristics of time deposit products, return calculation simulations, and technical tutorials on the deposit process. The results indicate a significant improvement in participants’ knowledge and skills in managing low-risk investments through digital banking services. This activity enhances financial literacy and promotes more rational investment decision-making among participants.